2008
DOI: 10.1111/j.1365-263x.2008.00921.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral health in preschool children with asthma

Abstract: Objective. The aim of the present study was to investigate oral health and its determinants in 3-and 6-year-old children with asthma. Methods and Subjects.Caries and gingivitis were examined in 127 asthmatic (all children with asthma in a selected area and born during a specific time period) and 117 matched, healthy control children.The parents were interviewed regarding various oral health-related factors.Results. The mean dfs (± standard deviation) in the 3-year-olds with asthma was 1.4 ± 3.2 compared with 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
57
0
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 13 publications
8
57
0
8
Order By: Relevance
“…It appears that the oral health of asthmatics is affected in different age groups, from early childhood to young adulthood. In recent studies by our research group, investigating the oral health of younger asthmatics, it was concluded that it was not the disease per se that caused a higher caries prevalence but rather caries-related factors, such as a lower salivary secretion rate, frequent mouthbreathing and a higher consumption of sugary drinks [8,9]. This is in line with the present study, including the same caries-related factors.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It appears that the oral health of asthmatics is affected in different age groups, from early childhood to young adulthood. In recent studies by our research group, investigating the oral health of younger asthmatics, it was concluded that it was not the disease per se that caused a higher caries prevalence but rather caries-related factors, such as a lower salivary secretion rate, frequent mouthbreathing and a higher consumption of sugary drinks [8,9]. This is in line with the present study, including the same caries-related factors.…”
Section: Discussionsupporting
confidence: 82%
“…The majority of these reports found that both children and adolescents with asthma run a greater risk of dental caries and/or gingival inflammation than healthy controls [5][6][7][8][9][10][11][12]. This impaired oral health may result in a foundation for further caries development and periodontal diseases later in life.…”
Section: Introductionmentioning
confidence: 99%
“…The possible cause of an increase in caries prevalence among asthmatic patients has been related to the use of beta 2-agonists in the treatment of asthma which leads to a reduction in the salivary flow. Stensson et al, 19 Shashikiran et al, 20 and McDerra et al 21 do not demonstrate a positive association between asthma and dental caries. GINA has subdivided asthma by severity, based on the level of symptoms, airflow limitation, and lung function variability, into four categories: Intermittent, mild persistent, moderate persistent, or severe persistent ( Table 9).…”
Section: Discussionmentioning
confidence: 99%
“…SSB consumption is associated with poor health, including conditions such as obesity (15) , CVD (16) , type 2 diabetes (15) and metabolic syndrome (15) . Interestingly, recent data also link SSB with airway health, specifically asthma (7,(17)(18)(19) . One recent cross-sectional study found that SSB consumption was positively associated with asthma in a sample of 16 907 Australian adults aged 16 years and older (7) .…”
mentioning
confidence: 99%